Constancy of the Court in the context of the current legislative amendments - Panchev, Tsvetomir (Law Journal of New Bulgarian University, 2022)
This article is an attempt to interpret the proposals for amendments of the Judiciary Act, prepared by the Ministry of Justice, containing regulations related to the closure of Specialized Public Prosecutor’s Office and the Specialized Criminal Courts there. In particular, the study focuses on the regulation related to the completion of pending court proceedings of specialized courts, through the prism of strict compliance with the well-known principle of constancy of the court in penal procedures. The author’s aim is to provide a complex of arguments to prove the fundamental importance of the principles of the Bulgarian criminal process, as an important basis of knowledge for planning and assessing the quality of each legislative initiative.